MENTAL HEALTH COUNSELING TO IMPROVE THE ROLE OF THE FAMILY IN CARE FOR ODGJ IN SUMBERWARU VILLAGE, EAST JAVA - Rahmawati, Dewi; Anjani, Soffia Dwi; Ambari, Yani; Ningsih, Arista Wahyu; Aristia, Bella Fevi; Klau, Ivan Charles Seran; Nurhidayah, Eka Putri (Universitas Airlangga, 2025)
The results of the 2023 Basic Health Research in East Java showed that 98.5% of severe ODGJ had received mental health services, but this achievement still did not meet the target. The imbalance between the increase in cases and the number of patients seeking treatment is a major challenge. One of the contributing factors is the lack of continuous monitoring by limited health workers. Therefore, this mental health counseling activity aims to increase the role of families in supporting the recovery of ODGJ patients through education and assistance. This activity was carried out in Sumberwaru Village for one day and involved 8 ODGJ families and 22 mothers of toddlers and the elderly. The methods used included counseling through lectures, interactive discussions, and question and answer sessions. Evaluation of success was carried out with a pre-test and post-test to measure the increase in participants' understanding before and after the activity. In addition, direct observation was carried out on family involvement in caring for patients, such as reminding them to take medication and taking them to the mental health post. The evaluation results showed an increase in participants' understanding from 69.33% in the pre-test to 90.66% in the post-test, indicating success in increasing family awareness of their role in accompanying ODGJ. In addition, families were more active in ensuring that patients received the necessary care. In conclusion, family-based counseling is effective in increasing family understanding and involvement in ODGJ care, so it can help prevent relapse and improve the patient's quality of life.